3D Modeling: From Technological Development to Generative AI - Fernandes, João Victor Silva (Farol, 2026)
This paper presents a partial outcome of doctoral research conducted alongside an outreach project by the Arts Extension and Research Laboratory (LEENA-UFES). Beyond delving into the technical and historiographical study of 3D modeling, the project seeks to understand how the use of generative artificial intelligence can contribute to the serialization and dynamic development of 3D models intended for printing. Thus, this article aims to explore the origins of 3D modeling within the context of the Cold War in the United States, investigating its historical-scientific development from the mid-20th century to its most recent evolutions. Furthermore, we seek to identify points of intersection between the application of 3D modeling as a contemporary sculpting technique and the machine-driven process of incorporating generative artificial intelligence into the sculptural creation process.
Keywords: 3D modeling; digital sculpture; generative artificial intelligence